Kostumiranje narodno-zabavnih ansamblov - Knific, Bojan (Traditiones, 2005)
<span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">V prispevku so obravnavani odrski oblačilni videz narodno-zabavnih ansamblov in prepoznane zakonitosti, ki so vplivale na razvoj tovrstnega kostumiranja. Najpomembnejšo vlogo je zaradi svoje odločitve, da se obleče v t. i. narodne noše, v petdesetih letih 20. stoletja imel Ansambel bratov Avsenik, t. i. narodna noša pa je zlasti v tujini postala in ostala obvezna spremljevalka slovenske narodno-zabavne glasbe. <span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">*** <span style="line-height: 115%; font-family: 'Helvetica','sans-serif'; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">What is interesting to observe and study in the field of polka music, apart from musical characteristics of this genre, is the visual appearance of it‘s performers, along with origin and use of the so called »national garb« as a substantial part of this genre. This style in fact came to it‘s own in the Fifties (20th Century), marked by the appearance of The ensemble of Avsenik Brothers along with a number of other similar ensembles. The decision to use the »national costume« as a part of their image proved to work in their favor and hereby became a hallmark of polka music both at home and abroad.